The The Influence of Motivation for Sharing GenZ Islamic Content on Social Media - Armiah Armiah (Mediator: Jurnal Komunikasi, 2023)
The high intensity of using gadgets in conveying da’wah messages shows that the internet is very effective. UIN students often like and post assembly announcements, video lectures, or motivational sentences on their social media. Some even volunteer at Aswaja Net and Al Jami. They produce and disseminate Islamic content. The behaviour of sharing Islamic content becomes attractive if it is related to their motivational background in sharing content with others. The initial hypothesis is that there is a desire to invite others to do good, provide benefits, remind each other, and prevent evil. This study uses a mix method approach. Data collection techniques by distributing Google form questionnaires and FGDs. Data analysis technique with multiple linear regression analysis. The results are based on a sample of 566 students, found that motivation and intensity simultaneously influence the behaviour of sharing Islamic content. The effect value of the independent variable on the dependent variable is 58.5%. The motivation for sharing Islamic content includes self-actualization motivation in preaching as much as 75.6%, and to get responses from others as much as 72.4%. Meanwhile, the intensity of accessing Islamic content was 45.9% 2-5 times per day and 41.3% accessed less than 10 minutes.